2017
DOI: 10.1097/mpg.0000000000001302
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Optimization Based on Therapeutic Drug Monitoring in Pediatric Inflammatory Bowel Disease

Abstract: We demonstrate that low IFX levels are associated with development of immunogenicity to IFX as measured by ATI. We demonstrate that interval shortening rather than dose escalation results in higher IFX levels. We suggest that given the high number of IFX levels below 3 μg/mL in patients, early IFX level evaluation or primary initiation of Q6 week dosing be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Some experts experienced that altering IFX injection to 5 mg/kg with 4-week intervals was sometimes effective in patients initially administered 10 mg/kg IFX at 8-week intervals. Shortening of the interval can be more effective than increasing the dose because the serum concentration of TNF-α inhibitors is maintained at stably high levels [12-14]. Although dose optimization based on the serum trough level is ideal, it is not covered by Japanese national health insurance and can only be measured in limited institutions.…”
Section: Summary Of the Meetingmentioning
confidence: 99%
“…Some experts experienced that altering IFX injection to 5 mg/kg with 4-week intervals was sometimes effective in patients initially administered 10 mg/kg IFX at 8-week intervals. Shortening of the interval can be more effective than increasing the dose because the serum concentration of TNF-α inhibitors is maintained at stably high levels [12-14]. Although dose optimization based on the serum trough level is ideal, it is not covered by Japanese national health insurance and can only be measured in limited institutions.…”
Section: Summary Of the Meetingmentioning
confidence: 99%
“…Several pediatric studies, however, reported TLs below the therapeutic range with a standard 5 mg/kg dose at an 8-week interval (25,27). Four studies comparing different age groups showed TLs to be lower in younger children with IBD compared to adolescents (25,29,37,43).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported that week 14 TLs may have predictive value for clinical remission without dose intensification during maintenance or deep remission (clinical remission with normal CRP) (21,46). Hofmekler et al (37) defined clinical outcome as the need for dose optimization and reported that 37% of children who required dose optimization had low TLs during maintenance (<3 mg/mL). Stein et al (49) reported that children who were still on IFX treatment after 12 months had higher 10-week median TLs compared to patients who had stopped IFX treatment.…”
Section: Clinical Outcome: Pharmacodynamicsmentioning
confidence: 99%
“…In children with moderate-to-severe UC, week 8 levels of serum IFX concentrations (≥41.1 μg/ml) were associated with greater proportions of patients achieving efficacy endpoints (clinical response: 92.9%; mucosal healing: 92.9%; and clinical remission: 64.3%) versus those with lower serum concentrations (<18.1 μg/ml; 53.9%, 53.9%, and 30.8%, respectively) 87 . A retrospective study from a tertiary care center demonstrated that interval shortening rather than dose escalation results in higher IFX levels, and the authors recommended a dose of every 6 weeks for optimizing levels 88 .…”
Section: Anti-tnfsmentioning
confidence: 99%